2019
DOI: 10.21203/rs.2.9386/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social work support and unmet social needs in life after stroke: a cross-sectional exploratory study

Abstract: Background: Stroke patients are often affected by long-term disabilities with needs concerning social issues. There is relatively little consideration of social recovery of patients and the support required to return to work, receive social benefits, participate in daily life activities, maintain contact with family and friends and to organize financial affairs. In our study we aimed to investigate if existing tools record social needs adequately. We analyzed the current provision of social support provided in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…All patients living with at least one relative had significantly higher SSQOL indices than those living alone or in nursing homes. Our research data are similar to the results of a study conducted in Portugal and Luxembourg that demonstrated a strong correlation between patient satisfaction and family integration in aphasia rehabilitation therapy [49] as well as other works [59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…All patients living with at least one relative had significantly higher SSQOL indices than those living alone or in nursing homes. Our research data are similar to the results of a study conducted in Portugal and Luxembourg that demonstrated a strong correlation between patient satisfaction and family integration in aphasia rehabilitation therapy [49] as well as other works [59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…Este é um cenário comum entre os cuidadores e o suporte de um assistente social seria fundamental para orientar sobre a busca de recursos sociais na rede assistencial, como o auxílio nanceiro, empréstimo ou doação de produtos (i.e., cadeira de rodas, camas, alimentação), entre outros. Este suporte social informativo pode contribuir para reduzir a sobrecarga e melhorar a qualidade de vida dos cuidadores familiares (26) .…”
Section: Resultsunclassified
“…Consequently, this suggests their usefulness as an indicator of the quality of life of stroke patients. In studies carried out by Khalid et al [12] the majority of patients were people with ischemic stroke (76.8%) with an age median of 59 (17) years. The time median since stroke was 13.83 months.…”
Section: Assessment Of Functional Capacitymentioning
confidence: 98%
“…A significantly greater number of patients with PTSD had depression (P < 0.001) and anxiety (P < 0.001) compared to patients without PTSD. In turn, Lehnerer et al [17] assessed their current offer of social support provided in long-term post-stroke care and the incidence of unmet social needs in the long term. They also determined whether these unmet needs were related to quality of life, caregiver burden, overall function and degree of disability, and stroke scale.…”
Section: Assessment Of Functional Capacitymentioning
confidence: 99%